2008
DOI: 10.1074/jbc.m804538200
|View full text |Cite
|
Sign up to set email alerts
|

Novel Bifunctional Natriuretic Peptides as Potential Therapeutics

Abstract: Synthetic atrial natriuretic peptide (carperitide) and B-type natriuretic peptide (BNP; nesiritide) are used to treat congestive heart failure. However, despite beneficial cardiac unloading properties, reductions in renal perfusion pressures limit their clinical effectiveness. Recently, CD-NP, a chimeric peptide composed of C-type natriuretic peptide (CNP) fused to the C-terminal tail of Dendroaspis natriuretic peptide (DNP), was shown to be more glomerular filtration rate-enhancing than BNP in dogs. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 21 publications
3
79
0
Order By: Relevance
“…These data are related to previous results from our group on the activation of GC-A and GC-B by CD-NP (Dickey et al, 2008). CD-NP is a designer natriuretic peptide consisting of the 15-residue carboxyl terminus of dendroaspis natriuretic peptide appended to the carboxyl terminus of CNP (Lisy et al, 2008) (Fig.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…These data are related to previous results from our group on the activation of GC-A and GC-B by CD-NP (Dickey et al, 2008). CD-NP is a designer natriuretic peptide consisting of the 15-residue carboxyl terminus of dendroaspis natriuretic peptide appended to the carboxyl terminus of CNP (Lisy et al, 2008) (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…Because CNP binds a different receptor than ANP or BNP, identical residues between CNP or ANP and BNP cannot determine binding specificity. Previous studies from our group suggested that triple substitutions in one of the two variable regions in the 17-amino acid ring of a C-terminally extended form of CNP, called CD-NP, modified the binding preference for GC-A and GC-B (Dickey et al, 2008). Here, we investigated the effect of single or double substitutions on the ability of BNP to activate GC-A and GC-B.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there has been an interest in using natriuretic peptides in heart failure therapy (Boerrigter et al, 2009), although studies have shown limited, if any, effects of the BNPanalog nesiritide (O'Connor et al, 2011). However, the use of a chimeric natriuretic peptide, CD-NP, with dual selectivity for both NPR-A and NPR-B receptors, has also been suggested in the treatment of heart failure (Dickey et al, 2008). No studies have compared the signaling pathways after BNP and CNP stimulation in failing hearts.…”
Section: Introductionmentioning
confidence: 99%
“…Human embryonic kidney 293 cells stably expressing human NPR-A or NPR-B or NPR-C were previously described (9). Binding of 125 I-ANP to HEK 293 cells stably expressing various natriuretic peptide receptors was performed as previously described (9).…”
Section: Expression Of Recombinant Asbnp Mature Peptide and Western Bmentioning
confidence: 99%